Multipotency and Immunomodulatory Benefits of Stem Cells From Human Exfoliated Deciduous Teeth - Guo, Rong; Yu, Jinhua (Frontiers in Dental Medicine, 2022)
Stem cells derived from human exfoliated deciduous teeth (SHEDs) are considered a promising cell population for cell-based or cell-free therapy and tissue engineering because of their proliferative, multipotency and immunomodulator. Based on recent studies, we find that SHEDs show the superior ability of nerve regeneration in addition to the potential of osteogenesis, odontogenesis owing to their derivation from the neural crest. Besides, much evidence suggests that SHEDs have a paracrine effect and can function as immunomodulatory regents attributing to their capability of secreting cytokines and extracellular vesicles. Here, we review the characteristic of SHEDs, their multipotency to regenerate damaged tissues, specifically concentrating on bones or nerves, following the paracrine activity or immunomodulatory benefits of their potential for clinical application in regenerative medicine.